Factors influencing postgraduate student satisfaction towards non-academic staff behaviour in UUM - Thibalatha, Sivalingam (2015)
This research examines the influence of responsiveness, reliability and assurance among non-academic staff behaviour in UUM on the outcomes of postgraduate student satisfaction. Few empirical studies have addressed the students satisfaction in UUM but most of the studies thus far only talks about student's satisfaction in general (regardless of undergraduate and postgraduate), thus this research looks into postgraduate student satisfaction (Dependent Variable) and aspects on Non-Academic Staff behaviour in specific. A total of 400 questionnaires was distributed to Postgraduate students in UUM, Sintok. Multiple regressions were applied on 271 completed questionnaires to the hypotheses listed in this research. The study has demonstrated that there exist a connection between non-academic staff behaviour and the level of satisfaction among the postgraduate students. The findings offer support for the value of right behaviour to achieve competitive advantage via upgrading of UUM's current service level.